(untitled) (Research, Society and Development, 2020)
It know that currently in the routine of dental offices the frequency of patients who use antithrombotic medications such as anticoagulants and antiplatelet agents is quite relevant, these drugs act to decrease blood coagulability, preventing thromboembolic problems from occurring. And with that it brings the diversity of thoughts in relation to performing dental surgical procedures. With the evolution of dentistry, it is possible to observe the diversity of existing protocols for the care of these patients, ranging from the change of heparin, reduction or pause of antithrombotic medication, to its maintenance, emphasizing the use of local hemostatic techniques. In view of the use of antithrombotic therapy by these individuals who started to make constant dental consultations, the purpose of this study was to analyze the most appropriate way to perform the care of these patients who are subjected to oral surgical procedures. The INR test is a calculation performed between the prothrombin time and the average of the normal coagulation interval, where it demonstrates that it is reliable to perform dental surgery if the INR is between 2 and 3.5. If it is higher than 5, it is not recommended to perform any procedure. Some authors claim that it is reliable to perform dental surgeries without major bleeding and in a safe manner, as long as the International Standardized List (INR) is included in the therapeutic levels. In this perspective, it was possible to analyze that maintenance on anticoagulant therapy, associated with the use of local hemostasis methods, represents the most appropriate protocol for surgical cases at an outpatient level.